Roadmaps for e-technology management - Yee, Choy Leong; Teoh, Kenny Guan Cheng; Yong, Hua Lung; Awang, Mat K. (2011)
This research aims to study the use of roadmaps in e-Technology management. e-Technology is becoming increasingly important in the new technological age. The effective management of e-Technology is the concern of many managers today. Many managers require appropriate methods or systems such as a roadmap, which can support the development and implementation of integrated strategic business, product and technology plans. Roadmaps have been widely used in industry. However, roadmaps consist of various types of format and use in different ways by many firms. The diverse ways of roadmap construction may be due to a lack of clear and accepted standards or formats for managers. This paper illustrates how roadmaps are use for e-Technology management in a firm. The firm has adopted roadmaps for analysing their R&D, technology, product and marketing plans. The paper has discovered many useful insights into managing e-Technology with roadmaps. The paper concludes with discussing implications to managers and academics.